2001
DOI: 10.1212/wnl.57.3.500
|View full text |Cite
|
Sign up to set email alerts
|

Current management of ALS

Abstract: These findings indicate that in the 3-year period prior to the publication of the AAN Practice Parameter, many but not all patients received the care that is recommended in that parameter; there were deficiencies, particularly in the key areas of gastrostomy and noninvasive positive pressure ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(58 citation statements)
references
References 13 publications
3
51
0
4
Order By: Relevance
“…Although the percentage of ALS patients that actually die following acute respiratory distress is small (0-3%), a large percentage of ALS patients are afraid of suffocation [3,6,9]. A retrospective study carried out in ALS caregivers, however, reported that 52% of ALS patients had moderate to severe choking episodes during the last month of their life [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the percentage of ALS patients that actually die following acute respiratory distress is small (0-3%), a large percentage of ALS patients are afraid of suffocation [3,6,9]. A retrospective study carried out in ALS caregivers, however, reported that 52% of ALS patients had moderate to severe choking episodes during the last month of their life [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, fewer than 5% of patients opt for tracheostomy and mechanical ventilation. 24,25 Factors that contribute to this opting out include the financial burden associated with daily maintenance, quality of life concerns for patient and caregiver, and uncertainty about when to remove a patient from the ventilator. 7,20 If a patient elects to undergo tracheostomy and mechanical ventilation, it is critical for clear criteria to be established regarding ventilator withdrawal.…”
Section: Aligning Treatment With Patient Preferencesmentioning
confidence: 99%
“…A Cochrane Library meta-analysis (including three doubleblind randomized placebo controlled trials by (Miller, 2002) suggests that riluzole provides a 9% gain in the probability of surviving one year and adds approximately 2 months to patient survival. Carbamazepine Phenytion Magnesium (Miller, et al, 1999;Andersen, et al, 2005) Physiotherapy Physical exercise Massage Hydrotherapy (Miller, et al, 1999;Andersen, et al, 2005 (Miller, et al, 1999;Andersen, et al, 2005) Amitriptyline (Bradley et al, 2001) Home suction device Nebulisation (Andersen, et al, 2005) injections of botulinum toxin into parotid glands (Giess et al, 2000/ Winterholler et al, 2001) irradiation of the salivary glands (Iannaccone et al, 1996;Stalpers and Moser, 2002) Persistent saliva and bronchial secretions -Bulbar weakness -Respiratory complications Carbocisteine Propranolol Metoprolol (Newall, et al, 1996) Home suction device hydrobromide (Miller, et al, 1999/Andersen, et al, 2005 Reduced intake of diary products, alcohol, and caffeine. …”
Section: Pharmacological Treatmentmentioning
confidence: 99%